Implementasi Metode Mimicry Memorization (Mim-Mem) Dalam Pembelajaran Mufrodat - Afrida Fatati; J. Sutarjo (Institut Agama Islam Negeri (IAIN) Metro, 2021)
This study aimed to analyze Arabic vocabulary mastery level of students and the process of implementing learning with the Mimicry Memorization method. This research method was quantitative research with an experimental approach. The study was conducted at Muhammadiyah Junior High School Pekalongan. Samples of this research were 25 students of class VII. Data collection methods were observation and tests. The observation method was used to get data on the process of implementing Arabic learning. The test method was aimed to students to get data on vocabulary mastery levels. Data analysis techniques used statistical tests with t test. The results showed that the Arabic learning process using the Mimicry Memorization (Mim-Mem) Method was able to overcome student learning difficulties, especially in the aspects of vocabulary mastery. The learning process became very enjoyable, students were actively involved in the learning process and students were very enthusiastic. Fun learning made students understand the lesson easily. The results of statistical analysis showed that the Mimicry Memorization (Mim-Mem) Method had a significant influence on vocabulary mastery.